Retorika Khitobah Santri Pondok Pesantren Salafiyah Al-Muawanah Dalam Kegiatan Kuliah Subuh - Hasanah, Sohihul; Sukayat, Tata; Dewi, Ratna (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The purpose of this research is to analyze and describe the ethos, pathos and logos used by the students during their sermons in their dawn lecture activities. The method used is descriptive method for conducting research that provides a description or description of the data obtained. The results of the study found that: (1) the ethos of the students' khitobah; santri have expertise in the form of knowledge, experience, trust and attractiveness, so that these characters can be said to be worthy of being preachers. (2) Phatos khitobah students; santri use high and low intonation, interspersed with humor at a reasonable level, body gestures, hand and eye movements. (3) Logos of the students' sermons; santri are relatively rational when listening to material by giving logical reasons and examples, using language that is easy and simple, and discussing the material presented in accordance with factual facts that occur in society.